Enhancing Vertical Trajectory Reconstruction in SASS-C: Advanced Segmentation, Outlier Detection, and Filtering Techniques - Daniel Amigo; David Sánchez Pedroche; Jesús García; José Manuel Molina; Jekaterina Trofimova; Emmanuel Voet; Benoît Van Bogaert (Aerospace)
This paper presents significant enhancements to the vertical reconstruction component of EUROCONTROL’s Surveillance Analysis Support System for ATC Centres (SASS-C). We introduce four key improvements: (1) a novel segmentation algorithm for more precise flight phase identification, (2) an improved invalid height detection process using LOWESS and sliding window analysis, (3) a protection mechanism against simultaneous measurements at the Kalman filter level, and (4) an optimized approach for smooth overshoot correction during segment transitions. These advancements address limitations in the current system, particularly in trajectory segmentation accuracy and robustness against measurement anomalies. Our methodology employs both synthetic and real-world data for comprehensive evaluation, ensuring performance under controlled and operational conditions. The results demonstrate substantial improvements in segmentation precision, outlier detection, and overall trajectory reconstruction quality. The invalid detection algorithm, while incurring a slight computational cost, significantly enhances trajectory accuracy. These enhancements contribute to more reliable air traffic analysis, supporting safer and more efficient airspace management. The paper concludes by discussing potential future work, including the application of machine learning techniques and the extension of these improvements to horizontal reconstruction processes.